Kawasaki disease with profound systemic vascular involvements: An insightful pediatric case - Naila Nadeem; Muhammad Nadeem Ahmad; Muhammad Haseeb Malik; Mallick Muhammad Zohaibuddin; Muhammad Ahmed; Faheemullah Khan; Hatem Eltaly; Uffan Zafar (Clinical Case Reports)
Key Clinical Message Kawasaki disease (KD), a self‐limiting vasculitis, can present with a broader spectrum of vascular involvements, necessitating early recognition and prompt management. This case exemplifies the importance of involving multiple teams on board in managing complex presentations of KD. It also highlights the importance of close monitoring for the progression of the disease spectrum as well as family education to ensure favorable outcomes. The case also emphasizes the importance of long‐term follow‐up and further research to understand the prognosis, early screening tools, and possible complications due to multi‐organ involvement in KD along with their management strategies. Abstract Kawasaki disease (KD) is a multisystem vascular inflammatory syndrome, which predominantly affects the small and medium vessels in children within the age group of less than 5 years. The most threatened complication is the development of coronary artery aneurysms (CAAs). We present an extremely rare case of KD in a 2‐month, 21‐day‐old male infant with extensive vascular involvement, expanding the disease spectrum beyond the involvement of coronary arteries. These included aneurysmal dilatations of both internal carotid arteries, the descending aorta, bilateral multilevel intercostal arteries, coeliac artery, superior mesenteric artery, and both renal arteries. Implementing a multidisciplinary approach with early treatment via intravenous immunoglobulin (IVIG) and dexamethasone proved to be most effective in the patient's management. Despite unique challenges such as severe coronary dilation and pseudomonas sepsis during the special care, the patient was stabilized and discharged after 11 days of hospital stay, highlighting the importance of early prompt management and a centered approach to evaluate in a broader spectrum. This case emphasizes the importance of long‐term follow‐up and further research to understand the prognosis, early screening tools, and possible complications due to multi‐organ involvement in KD along with their management strategies.